New Organic Dyes from Phthalonitrile via Interesting Nucleophilic Reactions - Zheng, Wei; Li, Cheng-Hui (Synlett, 2020)
Phthalonitrile (PN) is regarded mostly as an important precursor for phthalocyanine (Pc). However, the presence of two ortho triple bonds also endow PN with significant potential to form novel conjugated systems. Based on several unexpected nucleophilic reactions, our group has discovered novel applications of PN for the synthesis of asymmetric benzo-fused aza-BOIDPYs and new fused-ring phthalorubines (Pr). This Synpacts highlights our recent advances in this field.1 Introduction2 Benzo-Fused Aza-BODIPYs3 Phthalorubines4 Conclusion
Keywords: dyes; nucleophilic reactions; phthalonitrile; benzo-fused BODIPY; fused rings; phthalorubine